Acceptance and impact of Nirsevimab and the RSVpreF vaccine following implementation in Austria - Höck, Michaela; Borena, Wegene; Brunner, Jürgen; Wechselberger, Karina; Scheiring, Johanna; Ralser, Elisabeth; Pupp Peglow, Ulrike; Wöckinger, Peter; D’Costa, Elisabeth; Kaiser, Verena; Kapelari, Klaus; Gerold, Gisa; et al. (Frontiers in Public Health, 2025)
BackgroundSince summer 2024, passive immunization with nirsevimab (Beyfortus®) has been recommended for all infants in Austria to prevent severe respiratory syncytial virus (RSV) infection. Maternal vaccination with RSVpreF (Abrysvo®), which provides transplacental protection, became available in autumn 2023. The expected public health benefits of these preventive strategies depend largely on widespread acceptance; however, real-world data from Austria are unavailable.ObjectiveThis study aimed to assess the acceptance and impact of RSV immunization strategies during the 2024/2025 season in Tyrol, Austria.MethodsA retrospective study was conducted analyzing all live births at three Tyrolean maternity wards (Innsbruck, Hall, and Schwaz) from 5 December 2024 to 15 April 2025. Immunization rates were analyzed, and RSV-related hospitalization frequency and duration were compared to pre-pandemic seasons.ResultsOf 1,156 newborns, 57% received nirsevimab and 12% were protected by maternal RSVpreF protection, resulting in an overall coverage of almost 70%. RSV-related hospitalizations for infants under 1 year of age significantly decreased from 151 in pre-pandemic seasons to 47 in the post-nirsevimab season (p = 0.018). During the post-nirsevimab season, the median age at hospital admission was significantly higher (p < 0.001), and the length of stay was shorter (p = 0.031). Importantly, none of the hospitalized infants received nirsevimab, and only one was born to a vaccinated mother.ConclusionOur findings highlight the positive impact of both RSV immunization strategies—nirsevimab and RSVpreF vaccine—while underscoring the need to enhance public awareness and education to improve immunization rates. Future immunization programs must be strengthened to provide better protection for the pediatric population and reduce RSV-associated morbidity in early life.